Biosynthesis and molecular engineering of templated natural products. Issue 4 (11th August 2016) - Chen, Ming; Liu, Jingyu; Duan, Panpan; Li, Mulin; Liu, Wen
Abstract: Bioactive small molecules that are produced by living organisms, often referred to as natural products (NPs), historically play a critical role in the context of both medicinal chemistry and chemical biology. How nature creates these chemical entities with stunning structural complexity and diversity using a limited range of simple substrates has not been fully understood. Focusing on two types of NPs that share a highly evolvable 'template'-biosynthetic logic, we here provide specific examples to highlight the conceptual and technological leaps in NP biosynthesis and witness the area of progress since the beginning of the twenty-first century. The biosynthesis of polyketides, non-ribosomal peptides and their hybrids that share an assembly-line enzymology of modular multifunctional proteins exemplifies an extended 'central dogma' that correlates the genotype of catalysts with the chemotype of products; in parallel, post-translational modifications of ribosomally synthesized peptides involve a number of unusual biochemical mechanisms for molecular maturation. Understanding the biosynthetic processes of these templated NPs would largely facilitate the design, development and utilization of compatible biosynthetic machineries to address the challenge that often arises from structural complexity to the accessibility and efficiency of current chemical synthesis.